Synthesis of polyethylene glycol-functionalized multi-walled carbon nanotubes with a microwave-assisted approach for improved heat dissipation - Amiri, A.; Sadri, R.; Ahmadi, G.; Chew, B.T.; Kazi, S.N.; Shanbedi, M.; Alehashem, M.S. (2015)
In order to improve the dispersibility of multi-walled carbon nanotubes (MWCNT) in aqueous media, MWCNT were functionalized with tetrahydrofurfuryl polyethylene glycol (TFPEG) in a one-pot, fast and environmentally friendly method. To reduce defects and eliminate the acid-treatment stage, an electrophonic addition reaction under microwave irradiation was employed. Surface functionalization was analyzed by FTIR, Raman spectroscopy, thermogravimetric analysis (TGA). In addition, the morphology of TFPEG-treated MWCNT (PMWCNT) was investigated by transmission electron microscopy (TEM). After the functionalization phase, the convective heat transfer coefficient and pressure drop in PMWCNT-based water nanofluids with various weight concentrations were analyzed and compared with that of the base fluid. The results suggest that the addition of PMWCNT into the water improved the convective heat transfer coefficient significantly. The pressure drop of prepared PMWCNT-based water nanofluids showed an insignificant variation as compared with the base fluid and could result from good dispersivity of PMWCNT. According to the laminar flow results, as the weight concentration and Reynolds number increase, the convective heat transfer coefficient and pressure drop increase.